The Emerging Market for Corporate Control in India: Assessing (and Devising) Shark Repellents for India's Regulatory Environment - Abhinav Chandrachud (Washington University Global Studies Law Review, 2011)
The Article presents information on the inbound and domestic takeover activity in India. It further focuses on the shark repellent deal under the Indian regulations, which were earlier ruled out. It also informs about the strict regulations imposed by the Reserve Bank of India over financial acquisitions.
Keywords: Environmental regulations; Corporate governance; Emerging markets; Financial services industry – Mergers; Reserve Bank of India